2019
DOI: 10.1088/1612-202x/ab1916
|View full text |Cite
|
Sign up to set email alerts
|

Application of adaptive filters to improve online detection sensitivity of 13CO2 in a mixture with 12CO2 in expiratory air

Abstract: The use of adaptive Kalman and Wiener filters and the empirical mode decomposition algorithm for processing the experimental signal obtained by the tunable diode laser absorption spectroscopy method has been reported to improve the sensitivity of the measurement of 13 CO 2 content in human expiratory air. A laser diode, tunable in the range 4860-4880 cm −1 near the wavelength of 2 µm, is used as a source. It has shown that the application of these filters ensures a detection sensitivity of 13 CO 2 at the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…As noted in a series of publications, the tunable diode laser absorption spectroscopy (TDLAS) method, using a tunable diode laser (TDL) emitting near to the wavelength of 2 μm, is one of the most promising for solving a highly sensitive and highly accurate online measurement of 13 CO 2 mixed with 12 CO 2 in human expiratory air [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…As noted in a series of publications, the tunable diode laser absorption spectroscopy (TDLAS) method, using a tunable diode laser (TDL) emitting near to the wavelength of 2 μm, is one of the most promising for solving a highly sensitive and highly accurate online measurement of 13 CO 2 mixed with 12 CO 2 in human expiratory air [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The cell windows were made of potassium bromide, which is optically transparent in the studied spectral range. R (18), R(20), R(22), R(24), R(26), R(28), R(30), R(32), R(34) and R(36) vibration-rotation radiation curves of the 12 Figure 1 shows two sections of the transmission spectrum of a 12 C 16 O 2 and 13 C 16 O 2 mixture at pressures of 210.5 mbar and 15 mbar containing absorption lines of 12 C 16 O 2 and 13 C 16 O 2 ; along the horizontal axis there is the time scan of the signal recorded by the photodetector, which passed through the cuvette.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
“…Earlier, this method was used to measure the content of 13 C 16 O 2 (636) in a mixture with 12 C 16 O 2 (626) in exhaled air. Performed studies have shown that one of the most promising ranges for measurements is the region near a wavelength of 2 µm (frequency range: 4860-4880 sm −1 ), which contains a number of absorption curves of these molecules, to a minimum extent overlapping, and the experimental arrangement does not require complex and expensive equipment [18][19][20]. To accurately measure the content of 13 C 16 O 2 and 12 C 16 O 2 in the analyzed mixture, knowledge of the absorption constantvalues and their pressure dependence, since the measurements can be carried out at different pressures, are necessary.…”
Section: Figure 1bmentioning
confidence: 99%
“…One of the promising high-sensitive H 2 S detection methods may become the tunable diode laser absorption spectroscopy (TDLAS) based on the phenomenon of direct absorption of laser radiation by gas, previously implemented for some other substances, for instance, 13 CO 2 [20][21][22][23][24][25][26][27][28]. This method is characterized by high selective ability, making it possible to resolve vibrational-rotational absorption spectra of various substances mixed together.…”
Section: Introductionmentioning
confidence: 99%